Mekong cooperation frameworks and geopolitical dynamics: a Cambodian perspective - Kin Phea (Восточная Азия: факты и аналитика)
The Mekong River Basin, a lifeline for millions in Southeast Asia, faces a multifaceted challenge: balancing cooperation for sustainable development with the competing geopolitical interests of regional and global powers. This paper explores the Mekong Cooperation Frameworks (MCF), a web of partnerships between the Mekong countries and external actors. This paper delves into the strengths and weaknesses of various MCF frameworks, including the Mekong River Commission (MRC), Greater Mekong Subregion (GMS), Mekong-Ganga Cooperation (MGC), Mekong-Japan Cooperation (MJC), Lower Mekong Initiative (LMI), Mekong-Lancang Cooperation (MLC), and Mekong- Republic of Korea Cooperation (Mekong-ROK). Each framework offers unique approaches to infrastructure development, water resource management, and socio-economic progress, but also faces limitations. Beyond existing frameworks, this paper also provides suggestions for the characteristics of successful Mekong-Russia Cooperation (MRUC) within the MCF. The author further analyses the complex geopolitical landscape of the Mekong region. The Mekong countries must navigate the influence of China, a major player in infrastructure projects and water management, while also engaging with the United States, Japan, and other regional powers. Frameworks like the LMI and Friends of the Lower Mekong appear to counter China's dominance, while the MLC raises concerns about transparency in water resource management. This paper proposes some recommendations to ensure the Mekong River remains a symbol of regional cooperation and prosperity. Strengthening the MRC through enhanced regulatory power and fostering greater regional cooperation on water management and environmental protection is crucial. The author also emphasizes leveraging existing ASEAN mechanisms for collective action and advocating for a unified approach to the Mekong. Conclusively, this paper argues that navigating the geopolitical complexities of the Mekong region requires a delicate balancing act. By fostering cooperation within the MCF, strengthening regional institutions, and advocating for a unified approach, the Mekong countries can ensure the Mekong River serves as a bridge for a sustainable and prosperous future.